Effect of work hardening of cobalt in sintered carbide cutting tool on tool failure during interrupted cutting - Altan, Erhan; Uysal, Alper; Anac, Seref Han; Ozturk, Sabri (SPRINGER LONDON LTD, 2017)
In interrupted cutting, chips occur as intermittent and cutting tool may be damaged under severe variable loading. And it is known that the cutting forces cause transverse cracks on the rake face, and cutting tool may be damaged during interrupted cutting under mechanical and thermal fatigue in a short period of time. In this work, carbide inserts and forged SAE 4340 workpiece with axial slots were used in interrupted turning. The hardness values of some points on rake face near the cutting edge were measured, and cracks and failures on cutting tool were displayed by scanning electron microscopy (SEM). Additionally, milling experiments were conducted with carbide inserts on C45 medium carbon steel. In the interrupted cutting, the effect of work hardening of cobalt in sintered carbide cutting tool on tool failure was investigated. According to the results, micro hardness of sintered carbide cutting tool increased due to work hardening of cobalt, and this caused the micro crack formation on cutting tool.
Keywords: Interrupted cutting; Work hardening of cobalt; Carbide tool; Fatigue; TEMPERATURES; WEAR; Automation & Control Systems; Engineering